PEMBINAAN KADER PHBS PADA ANAK SEKOLAH DASAR DI SDN INPRES ENEMAWIRA KECAMATAN TABUKAN UTARA - Kasaluhe, Meityn; Pramardika, Dhito Dwi; Sambeka, Yana; Tanod, Wendy Alexander; Cahyono, Eko (Jurnal Ilmiah Tatengkorang, 2024)
Clean and Healthy Living Behavior (PHBS) in schools now feels even more crucial considering that children will soon return to school during the new normal of the corona virus pandemic. The benefit of PHBS in schools is to create a clean and healthy environment. Community service activities were carried out for students of SDN Inpres Enemawira, Tabukan Utara District, Sangihe Islands Regency. The purpose of implementing this activity is to increase students' knowledge about PHBS at school, especially during the adaptation period of new habits in preventing transmission of COVID-19. The flow of implementing community service activities consists of several steps, namely: (1) exploration and initial survey, (2) determination of implementation, (3) implementation, and (4) evaluation. The implementation of community service has a positive impact on students, namely increasing knowledge about PHBS and students being able to independently practice various indicators of PHBS at school. Perilaku Hidup Bersih dan Sehat (PHBS) di sekolah kini terasa semakin krusial mengingat anak-anak akan segera kembali bersekolah di masa new normal pandemi virus corona. Manfaat PHBS di sekolah adalah menciptakan lingkungan yang bersih dan sehat. Kegiatan pengabdian masyarakat dilakukan pada siswa SDN Inpres Enemawira Kecamatan Tabukan Utara Kabupaten Kepulauan Sangihe. Tujuan pelaksanaan kegiatan ini adalah untuk meningkatkan pengetahuan siswa tentang PHBS di sekolah terutama pada masa adaptasi kebiasaan baru dalam mencegah penularan COVID-19. Alur pelaksanaan kegiatan pengabdian kepada masyarakat terdiri dari beberapa Langkah, yaitu: (1) penjajakan dan survei awal, (2) penetapan pelaksanaan, (3) pelaksanaan, dan (4) evaluasi. Pelaksanaan pengabdian masyarakat memberikan dampak positif bagi siswa yakni peningkatan pengetahuan tentang PHBS dan siswa mampu secara mandiri mempraktikkan berbagai indikator PHBS di sekolah.